Study of user experience of an objective test (QbTest) to aid ADHD assessment and medication management: a multi-methods approach. Issue 1 (December 2017) - Hall, Charlotte; Valentine, Althea; Walker, Gemma; Ball, Harriet; Cogger, Heather; Daley, David; Groom, Madeleine; Sayal, Kapil; Hollis, Chris
Abstract Background The diagnosis and monitoring of Attention deficit hyperactivity disorder (ADHD) typically relies on subjective reports and observations. Objective continuous performance tests (CPTs) have been incorporated into some services to support clinical decision making. However, the feasibility and acceptability of adding such a test into routine practice is unknown. The study aimed to investigate the feasibility and acceptability of adding an objective computerised test to the routine assessment and monitoring of attention deficit hyperactivity disorder (ADHD). Methods Semi-structured interviews were conducted with clinicians (n = 10) and families (parents/young people, n = 20) who participated in a randomised controlled trial. Additionally, the same clinicians (n = 10) and families (n = 76) completed a survey assessing their experience of the QbTest. The study took place in child and adolescent mental health and community paediatric clinics across the UK. Interview transcripts were thematically analysed. Results Interviewed clinicians and families valued the QbTest for providing an objective, valid assessment of symptoms. The QbTest was noted to facilitate communication between clinicians, families and schools. However, whereas clinicians were more unanimous on the usefulness of the QbTest, survey findings showed that, although the majority of families found the test useful, less than half felt the QbTest helped them understand the clinician's decision making around diagnosis and medication. The QbTest was seen as a potentially valuable tool to use early in the assessment process to streamline the care pathway. Although clinicians were conscious of the additional costs, these could be offset by reductions in time to diagnosis and the delivery of the test by a Healthcare Assistant. Conclusions The findings indicate the QbTest is an acceptable and feasible tool to implement in routine clinical settings. Clinicians should be mindful to discuss the QbTest results with families to enable their understanding and engagement with the process. Further findings from definitive trials are required to understand the cost/benefit; however, the findings from this study support the feasibility and acceptability of integrating QbTest in the ADHD care pathway. Trial registration The findings form the implementation component of the Assessing QbTest Utility in ADHD (AQUA) Trial which is registered with the ISRCTN registry (ISRCTN11727351, retrospectively registered 04 July 2016) and clinicaltrials.gov (NCT02209116, registered 04 August 2014).